RETRACTED : The Effect of Store Atmosphere, Advertising and Word of Mouth on Customer Repurchase Interest at KFC in Margonda Depok - Silvia Hanisa; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the influence of store atmosphere, advertising and word of mouth variables on the interest in repurchasing customers at KFC in Depok Margonda. This study uses primary data obtained from the distribution of questionnaires as many as 100 KFC customers in Margonda Depok with multiple linear regression methods that are processed using SPSS version 24.0 software. The results of this study indicate that between store atmosphere, advertising and word of mouth have a positive and significant effect on the interest in repurchasing customers at KFC in Depok Margonda.